Improvement of nurses’ clinical practice in neonatal pain management: A Protocol of Evidence-Based Intervention - Razieh Talebi; Mahnaz Modanloo; Fatemeh Heydari; Neda Mehrdad; Abbasali Keshtkar; Homeira khoddam (Journal of Research Development in Nursing and Midwifery, 2022)
Background: Despite the expansion of knowledge of neonatal pain assessment and management, there is still a considerable gap between nurses' clinical practices in Iran and available evidence. The aim of this study was to develop an evidence-based protocol for neonatal pain management and to evaluate its effectiveness on nurses' clinical practice. Methods: The present study will be based on the Johns Hopkins nursing evidence-based practice (JHNEBP) model and the three stages of practice question and project planning, evidence, and translation (PET). In this way, after forming an interprofessional team, clinical practice questions will be defined, and the main stakeholders will be identified. Then, the types, levels, and quality of evidence will be assessed to summarize their final strength using the proposed tools of the model, and finally, recommendations will be developed. In the translation phase, the recommendations will be implemented during a stepped wedge cluster randomized trial, and its implications for nursing practices in the management of pain in hospitalized neonates will be evaluated. Results: The results of this study will lead to the production of an operational and applicable protocol in the management of pain in hospitalized neonates. It can provide the basis for improving the clinical practice of nurses and subsequently improving the quality of neonatal care. Conclusion: One of the strengths of this study is the use of an interprofessional team approach, considering the clients' priorities, and the improvement of organizational culture in order to endeavor for knowledge translation and change in clinical practice.